TEKNOLOGI BIOCHAR MEMANFAATKAN LIMBAH PERTANIAN UNTUK BUDIDAYA PERTANIAN DI DESA IBRU KABUPATEN MUARO JAMBI - Wiskandar Wiskandar; Ajidirman Ajidirman; Zurhalena Zurhalena; Heri Junedi (LPPM Universitas Al Muslim, 2024)
Tunas Makmur Farmers Group I of Ibru Village, Mestong District, Muaro Jambi Regency, Jambi Province has not yet made optimal use of a large amount of agricultural, plantation and industrial waste, due to farmers' lack of knowledge about biochar and its use to improve soil productivity. For this reason, the implementing team offers an easy, cheap and sustainable solution to manage and utilize abundant sources that can be used as a source of biochar. The objectives of implementing this community service activity can be achieved through: 1) counseling and training about the benefits of biochar to improve the physical and chemical properties of soil, 2) demonstration of making biochar from agricultural, plantation and industrial waste using drum pyrolysis, 3) assistance in calculating the dose given and application in the field through demonstrations on partner land on how to use biochars properly. Partners in this activity earn their main income from being food crop and plantation farmers. Agricultural, plantation and industrial waste is usually piled up on land and wasted because farmers do not yet have knowledge about the benefits of this waste. After conducting socialization and education through counseling and demonstrations about making biochar from agricultural and industrial waste, farmers have the motivation to use this waste as a source of soil carbon and as a soil conditioner.